2020
DOI: 10.1515/opag-2020-0065
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal normalized difference vegetation index responses to air temperature and precipitation in Baghdad

Abstract: The spatial distribution of urban vegetation cover is strongly related to climatological conditions, which play a vital role in urban cooling via shading and reducing ground surface temperature and effective strategy in mitigation urban heat island. Based on the Landsat satellite images, the quantitative normalized difference vegetation index (NDVI) was spatially mapped at two times for each year during 2008, 2013, 2019 in Baghdad. The NDVI values ranged from −1 to +1 with considering values larger than 0.2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
1
16
1
Order By: Relevance
“…The NDVI mentioned values were calculated using Landsat remote sensing images with a resolution of 30 m by 30 m which is moderateresolution data that can represent the properties of vegetation coverage in a specific area. The choice of fine resolution will aid in not only increasing the accuracy of field features but also in improving the efficiency of crop and hydrological models [70], resulting in more conclusive outputs and planners in pertaining vegetation cover in this study.…”
Section: Ndvi Derivationmentioning
confidence: 99%
“…The NDVI mentioned values were calculated using Landsat remote sensing images with a resolution of 30 m by 30 m which is moderateresolution data that can represent the properties of vegetation coverage in a specific area. The choice of fine resolution will aid in not only increasing the accuracy of field features but also in improving the efficiency of crop and hydrological models [70], resulting in more conclusive outputs and planners in pertaining vegetation cover in this study.…”
Section: Ndvi Derivationmentioning
confidence: 99%
“…As the value increases towards +1 or increasing positive NDVI values indicate the dense vegetation (vegetated the plant canopy), and close to zero or decreasing negative values (-1) indicates the non-vegetation surface such as water and bare ground [92]. A high positive value of NDVI is also computed from vegetated agricultural cover crops [93]. NDVI is calculated based on the difference in the ratio of Red (R) and near-infrared (NIR) reflectance, equations ( 9) and ( 10 The study site is found in semi-arid region, where climate variables are limiting factors for vegetation cover determination.…”
Section: Normalized Difference Vegetation Index (Ndvi) Analysismentioning
confidence: 99%
“…(1) Difference Vegetation Index DVI DVI values range from 0 to 1, where 0 represents no vegetation coverage; 1 represents a high degree of vegetation coverage [8][9].…”
Section: Commonly Used Vegetation Indicesmentioning
confidence: 99%
“…(1) Univariate linear model Use statistical software to generate a scatter plot from the data, add a linear trend line, and fit these scatter points to a straight line to ensure that the sum of the vertical distances from the scatter points to the straight line is the smallest [16][17]. In the establishment of a univariate linear model of grassland aboveground biomass, the measured grassland aboveground biomass is selected as the dependent variable, and the NDVI and RVI of the coordinate points corresponding to the measured value in the remote sensing image are selected as independent variables, and the univariate linear regression equation is:…”
Section: Establishment Of Grassland Aboveground Biomass Model Based O...mentioning
confidence: 99%